Natural organic matter in water characterization and treatment methods - Sillanpää, Mika E. T. (Butterworth-Heinemann, 2015)
An essential resource containing the latest breakthroughs in the characterization, treatment and removal of Natural Organic Matter (NOM) from drinking water, Natural Organic Matter in Waters: Characterization and Treatment Methods focuses on advance filtration and treatment options, and processes for reducing disinfection by-products. Based on the author's years of research and field experience, this book begins with the characterization of NOM including: general parameters, isolation and concentration, fractionation, composition and structural analysis and biological testing. This is followed by removal methods such as inorganic coagulants, polyelectrolytes and composite coagulants. Electrochemical and membranes removal methods such as: electrocoagulation, electrochemical oxidation, microfiltration and ultrafiltration, nanofiltration and membrane fouling.